COMPARATIVE PROFESSIONAL EDUCATION IN UKRAINE: CURRENT STATE, CHALLENGES, PROSPECTS - Svitlana Sysoieva (National Academy of Educational Sciences of Ukraine, 2018)
The article presents a quantitative and qualitative analysis of comparative studies on professional education in Ukraine since the years of independence (since 1991); the consideration of the concept of "comparative professional education", the main provisions of its methodology; the analysis of the tasks and specifics of comparative studies in the field of professional education. The article shows that the specificity of comparative professional education requires an interdisciplinary approach to research, taking into account external factors (historical, social, cultural, economic, political, etc.) of influence on the system, tendencies, content, technology, forms and methods of professional education in foreign countries that is possible to carry out on the principles of Educology.